A higher degree of expression of DNA methyl transferase 1 in cervical cancer is associated with poor survival outcome - Piyathilake CJ; Badiga S; Borak SG; Weragoda J; Bae S; Matthews R; Bell WC; Partridge EE (Dove Medical Press, 2017)
Chandrika J Piyathilake,1 Suguna Badiga,1 Samuel G Borak,2 Janaka Weragoda,1 Sejong Bae,3 Roland Matthews,4 Walter C Bell,2 Edward E Partridge5 1Department of Nutrition Sciences, 2Department of Pathology, 3Department of Medicine, The University of Alabama at Birmingham, Birmingham, AL, 4Department of Obstetrics and Gynecology, Morehouse School of Medicine, Atlanta, GA, 5Comprehensive Cancer Center, The University of Alabama at Birmingham, Birmingham, AL, USA Background: Even though novel therapies based on aberrant DNA methylation could be of particular importance for the treatment of cervical cancer (CC) because the oncoproteins E6/E7 of high-risk human papillomaviruses, the causative agents for developing CC, have the capacity to bind and upregulate DNA methyltransferases (DNMTs), to our knowledge, no previous studies have evaluated the expression of this enzyme in CC in relation to survival outcomes. The purpose of the study was to evaluate the expression of DNMT1 in CC and its association with survival outcomes.Methods: The study population consisted of 76 women treated for primary CC and followed up by the University of Alabama at Birmingham (UAB) cancer registry. The expression of DNMT1 was examined using immunohistochemistry, and the degree of expression of DNMT1 was expressed as a percentage of cells positive for DNMT1 and its intensity. Cox proportional hazards model was used to assess the relationship between the degree of expression of DNMT1 and overall survival after adjusting for relevant covariates.Results: The expression of DNMT1 was significantly higher in CC cells compared to that in the normal cervical epithelium. A higher percentage of cells positive for DNMT1 and a higher intensity score for DNMT1 were significantly associated with poor survival outcome (hazard ratio [HR] =4.3, P=0.03 and HR =4.9, P=0.02, respectively).Conclusion: Our findings suggested that the degree of expression of DNMT1 could be considered as a target in the epigenetic treatment of CC. Replication of our results in other study populations with CC could create the opportunity of using DNMT inhibitors to treat CC. Keywords: DNMT1, cervical cancer, survival outcome